1% Tetracaine hydrochloride injection pure solution aerosol inhalation combined with oral administration of dyclonine hydrochloride mucilage as upper airway anesthesia for bronchoscopy: A randomized controlled trial. (5th December 2019) - Wang, Ning; Jin, Faguang; Liu, Wei; Dang, ShaoKang; Wang, Yan; Yan, Yan; Wu, GuanPing
Abstract: Background: During the bronchoscopy process, successful passage of the tracheoscope through the glottis can affect the following procedure of bronchoscopy. Therefore, safer, more effective and less painful anesthesia methods are particularly important for the bronchoscopy success rate. Objective: This study aimed to evaluate the efficacy of 1% tetracaine hydrochloride injection pure solution aerosol inhalation combined with oral administration of dyclonine hydrochloride mucilage during bronchoscopy. Methods: Patients who need bronchoscopy or bronchoscope treatment were randomly assigned to two groups; group A received pure tetracaine hydrochloride injection solution (3 mL of 1% tetracaine hydrochloride) aerosol inhalation combined with oral 5 mL of dyclonine hydrochloride mucilage and group B received diluted tetracaine hydrochloride injection (3 mL of 1% tetracaine hydrochloride injection + 3 mL of sterile water for injection) aerosol inhalation combined with oral 5 mL of dyclonine hydrochloride mucilage. The anesthetic effect and adverse reactions of these groups were observed and compared. Result: A total of 523 patients were randomized. The results showed that patient's tolerance, cough response, glottis opening during the bronchoscope into the glottis and the time required to the tracheoscope pass through the glottis were obviously significantly better in group A than in group B. Vital signs including blood pressure, heart rate and pulse oxygen saturation were more stable in group A than in group B. Conclusion: The 1% tetracaine hydrochloride injection pure liquid aerosol inhalation combined with oral administration of dyclonine hydrochloride mucilage as upper airway anesthesia is effective and safe for bronchoscopy. This method of local anesthesia is worthy of clinical application.